(untitled) (Research, Society and Development, 2022)
Chronic lung diseases can potentially lead to limitation in patient’s daily activities and poor quality of life. Pulmonary Rehabilitation (PR) consists in a comprehensive and individualized care which aims to improve patient’s physical and psychological conditioning and can be used on the management of different lung diseases. The evaluation of the quality of life and functional exercise capacity of patients who underwent PR allows quantifying the effect of the intervention and the response to treatment. Thus, the study aimed to evaluate the impact of a Pulmonary Rehabilitation Program (PRP) on the quality of life and functional exercise capacity of patients with chronic lung diseases, seeking to determine the presence of Minimal Important Difference (MID) at the end of the rehabilitation period. It’s a retrospective case series performed by collecting data from 37 patients with chronic lung diseases who underwent a PRP between 2016 and 2019 in a tertiary care center in São Luis, Maranhão. It was noted that patients who concluded the PRP obtained significant improvement in Saint George Respiratory Questionnaire (SGRQ) score and in the distance covered in the Six Minute Walk Test (6MWT). In this last one, nearly half (48,6%) of the patients obtained MID, mostly represented by the group diagnosed with Chronic Obstructive Pulmonary Disease (COPD). Therefore, we concluded that patients with chronic lung diseases who underwent PR may achieved favorable clinical outcomes, improving exercise capacity and quality of life.